Ultrasound nanotheranostics in fighting cancer: Advances and prospects. (1st February 2020) - Zhou, Li-Qiang; Li, Pan; Cui, Xin-Wu; Dietrich, Christoph F.
Abstract: The intrinsic limits of conventional ultrasound microbubble contrast agent greatly promoted the development and application of various nanomaterials for more efficient cancer ultrasound theranostics. Considerable successes have been achieved in the field of ultrasound molecular imaging and targeted therapy for tumor based on nanoparticulate theranostic agents. This review summarizes and discusses the emerging development on exploring organic and inorganic nanomaterials for ultrasound-based tumor diagnositic applications, and as synergistic agents for ultrasound targeted therapy in fighting cancer. The relationship between structure/composition and functionality of nanomaterials for ultrasound theranostic is discussed and revealed in detail. Finally, the further development and challenges facing clinical implementation of ultrasound nanomedicine are discussed. As a highly promising and valuable tumor-specific theranostic methodology, it is believed that ultrasound nanomedicine would pave a novel but efficient way for combating cancer. Graphical abstract: The intrinsic limits of conventional ultrasound microbubble contrast agent greatly promoted the development and application of various nanomaterials for more efficient cancer ultrasound theranostics. Considerable successes have been achieved in the field of ultrasound molecular imaging and targeted therapy for tumor based on nanoparticulate theranostic agents. This review summarizes and discusses the emerging development on exploring organic and inorganic nanomaterials for ultrasound-based tumor diagnositic applications, and as synergistic agents for ultrasound targeted therapy in fighting cancer. The relationship between structure/composition and functionality of nanomaterials for ultrasound theranostic is discussed and revealed in detail. Finally, the further development and challenges facing clinical implementation of ultrasound nanomedicine are discussed. As a highly promising and valuable tumor-specific theranostic methodology, it is believed that ultrasound nanomedicine would pave a novel but efficient way for combating cancer. Image 1 Highlights: Overviewing the most representative nanoplatforms for specific ultrasound-responsive theranostic applications on fighting cancer. Revealing the relationship between structure/composition and functionality of versatile nanoplatforms for ultrasound theranostic of cancer. Discussing of the development and challenges facing clinical implementation of ultrasound-responsive nanomedicine in combating cancers.